DIFFICULTIES IN ONLINE LEARNING DURING COVID-19 PANDEMIC: PERCEPTIONS OF EFL STUDENTS OF UIN ALAUDDIN MAKASSAR - Salman, Muflih Anugrah; Kaharuddin, Andi; Multazam (Journal of Islam and Science, 2022)
Preventing the COVID-19 spreading and transmitting widely, the educational institution has forced to make transition from conventional learning to online learning. The adaptation of online learning has presented many difficulties. Students in online learning faced difficulties that they might never encountered before in a traditional teaching and learning environment. This research investigated the difficulties in online learning during the COVID-19 pandemic according to students’ perception. The method of this research is qualitative and the instruments used were questionnaire and interview involving ten participants from the fifth semester students at EED of UIN Alauddin Makassar. The findings show that all the participants had difficulties during online learning and those difficulties affected their learning performance. There are nine areas of online learning difficulties; (1) difficulty to focus due to distractions, (2) problem with internet connectivity, (3) difficult to understand learning content, (4) lack motivation due to absence face to face contact, (5) various learning method employed by lecturers, (6) slow personal devices, (7) lack of technical skill in using online learning, (8) limited broadband data, and (9) difficult to work in group.